Treatment with MG-132 and TSA induced apoptosis in OS-RC-2 cells by increasing oxidative stress and decreasing the expression of NF- kappa B - MIQING XU; HUI XIE; YUN ZHONG; JUNJIAN MA; SHIMING LIU; HUI YANG (Nusantara Bioscience, 2015)
Abstract. Xu M, Xie H, Zhong Y, Ma J, Liu S, Yang H. 2015. Treatment with MG-132 and TSA induced apoptosis in OS-RC-2 cells by increasing oxidative stress and decreasing the expression of NF-kappa B. Nusantara Bioscience 7: 20-25. Here we assessed the effect of the proteasome inhibitor MG-132 alone or in combination with the histone deacetylase inhibitor TSA on human renal cell on human renal cell carcinoma cells in vitro and we explored the underlying molecular mechanisms.OS-RC-2 cells were treated byMG-132 alone or in combination with TSA and/or NAc. The MTT assay and flow cytometry (FCM) were used to determine cell viability, ROS levels, and apoptosis. Expression of Bax and NF-kappa B p65 proteins was quantified by Western blotting. MG-132significantly increased the level of ROS, inhibited cell growth and induced apoptosis in a dose- and time-dependent manner. Both ROS and apoptosis were further increased following the combined addition of MG132 and TSA. In all cases, expression of p65 was down-regulated. MG-132 alone or in combination with TSA induced apoptosis in OS-RC-2 cells through the generation of ROS and the down-regulation of p65 expression.